Modernisasi Pendidikan Islam di Indonesia (Studi Komparasi Mahmud Yunus dan Azyumardi Azra) - Zulfadhilah Zulfadhilah; Rini Rahman (AS-SABIQUN, 2022)
One of the main aspects of human life is education. This cannot be separated from life, starting from the human being in the womb until returning to the creator. Seeing that there is still Islamic education that does not achieve its goals and does not keep up with the times, therefore the leaders of Islamic education immediately act to resolve this. Mahmud Yunus is an Islamic education figure who seeks to renew Islamic education. In addition, another character who made updates was Azyumardi Azra. Based on this, the researchers are interested in making comparisons or comparisons of the thoughts of the two figures. Researchers will make comparisons or comparisons specifically in terms of modernizing goals, curricula and educational institutions with the research title "Modernization of Islamic Education in Indonesia (Comparative Study of Mahmud Yunus and Azyumardi Azra)”The type of research used in this research is library research, which is the process of systematically searching and compiling data obtained from various literatures, both from primary and secondary sources.The results of research on the modernization of Islamic education are: 1) According to Mahmud Yunus, it is trying to integrate religious knowledge and general science in Islamic education. 2) Azyumardi Azra argues that the modernization of Islamic education must follow the current developments. 3) The similarity of thoughts between Mahmud Yunus and Azyumardi Azra is that they want a combination of religious knowledge and general science and must adapt to the demands of an increasingly advanced era. 4) The difference between Mahmud Yunus and Azyumardi Azra's thoughts lies in the groupings divided by each character.